Comparison of Anodic TiO2-Nanotube Membranes used for Frontside-Illuminated Dye-Sensitized Solar Cells - Mohammadpour, Fatemeh; Moradi, Mahmood; Cha, Gi; So, Seulgi; Lee, Kiyoung; Altomare, Marco; Schmuki, Patrik (ChemElectroChem, 2015)
In the present work we compare TiO2-nanotube lift-off strategies for the construction of frontside-illuminated dye-sensitized solar cells (DSSCs). Anodic nanotube layers were detached from the metallic back contact by using different techniques and transferred onto a fluorine-doped tin oxide substrate. We show that if we use an optimized potential step treatment to fabricate membranes, DSSC efficiencies can be significantly increased ( extgreekh>8 %). The improved efficiency is ascribed to higher specific dye loading and enhanced electron-transport properties of optimally fabricated TiO2-nanotube membranes.
EAM Import::2019-03-13